Income-related inequalities in unmet dental care needs in Spain: traces left by the Great Recession - Rosa M. Urbanos-Garrido (BMC, 2020)
Abstract Background Dental health is an important component of general health. Socioeconomic inequalities in unmet dental care needs have been identified in the literature, but some knowledge gaps persist. This paper tries to identify the determinants of income-related inequality in unmet need for dental care and the reasons for its recent evolution in Spain, and it inquires about the traces left by the Great Recession. Methods Data from the EU-SILC forming a decade (2007-2017) were used. Income-related inequalities for three years were measured by calculating corrected concentration indices (CCI), which were further decomposed in order to compute the contribution of different factors to inequality. An Oaxaca-type decomposition approach was also used to analyze the origin of changes over time. Men and women were analyzed separately. Results Pro-rich inequality in unmet dental care needs significantly increased over time (CCI 2007: − 0.0272 and − 0.0334 for males and females, respectively; CCI 2017: − 0.0704 and − 0.0776; p < 0.001). Inequality showed a clear "pro-cycle" pattern, growing during the Great Recession and starting to decrease just after the economic recovery began. Gender differences only were significant for 2009 (p = 0.004) and 2014 (p = 0.063). Income was the main determinant of inequality and of its variation along time -particularly for women-, followed by far by unemployment -particularly for men-; the contributions of both were mainly due to changes in elasticites. Conclusions The Great Recession left its trace in form of a higher inequality in the access to dental care. Also, unmet need for dental care, as well as its inequality, became more sensitive to the ability to pay and to unemployment along recent years. To broaden public coverage of dental care for vulnerable groups, such as low-income/unemployed people with high oral health needs, would help to prevent further growth of inequality.